2022
DOI: 10.1098/rspb.2022.0804
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive specialization of a unique sponge body from the Cambrian Qingjiang biota

Abstract: Sponge fossils from the Cambrian black shales have attracted attention from both palaeontologists and geochemists for many years in terms of their high diversity, beautiful preservation and perplexing adaptation to inhospitable living environments. However, the body shape of these sponges, which contributes to deciphering adaptive evolution, has not been scrutinized. New complete specimens of the hexactinellid sponge Sanshapentella tentoriformis sp. nov. from the Qingjiang biota (black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…These clusters 3A, C). The clusters, especially those with tightly contacted spicules, likely functioned in supporting and strengthening the main body, reminiscent of the large dermal pentactines in the coeval sponge Sanshapentella (Mehl & Erdtmann 1994;Luo et al 2021;Yun et al 2022). However, the diactine clusters herein are distinct from the dermal pentactines both in detailed structure and orientation, since the large dermal pentactines of Sanshapentella are composed of four long rays inserting into the body and a tiny fifth ray protruding out the body (Yun et al 2022).…”
Section: Skeletal Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…These clusters 3A, C). The clusters, especially those with tightly contacted spicules, likely functioned in supporting and strengthening the main body, reminiscent of the large dermal pentactines in the coeval sponge Sanshapentella (Mehl & Erdtmann 1994;Luo et al 2021;Yun et al 2022). However, the diactine clusters herein are distinct from the dermal pentactines both in detailed structure and orientation, since the large dermal pentactines of Sanshapentella are composed of four long rays inserting into the body and a tiny fifth ray protruding out the body (Yun et al 2022).…”
Section: Skeletal Architecturementioning
confidence: 99%
“…The earliest diverse articulated body fossils of sponges, which could shed more light on the evolution of sponge morphology and adaptive strategies, were discovered from the Cambrian Stage 3 Burgess Shaletype Lagerstätten (e.g. Rigby & Hou 1995;Wu et al 2014;Botting & Peel 2016;Luo et al 2020), and noticeably, fossil assemblages have been found in the early Cambrian black shales (Steiner et al 1993;Yuan et al 2002;Xiao et al 2005;Yang et al 2010;Yun et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early Cambrian witnessed a great burst in diversity of animal body plans and biomineralized shell architectures around half a billion years ago ( Briggs, 2015 ; Erwin, 2015 ; Erwin, 2020 ; Budd and Jackson, 2016 ; Murdock, 2020 ; Yun et al, 2021 ; Zhang and Shu, 2021 ; Zhang et al, 2021c ). The novel process of biologically-controlled mineralization producing organic-inorganic composites (hard skeletons) in complex animals had played a vital role in the survival and fitness of early clades ( Balthasar, 2009 ; Cuif et al, 2010 ; Li et al, 2022 ; Skovsted et al, 2008 ; Yun et al, 2022 ), and in turn built the fundamental blocks of complex marine ecosystems ( Bicknell and Paterson, 2018 ; Buatois et al, 2020 ; Chen et al, 2022 ; Zhang et al, 2010 ; Zhang et al, 2020a ). Since the early Cambrian, this adaptive evolution has been demonstrated and continuously preserved in brachiopods, one of the key members of the Cambrian Evolutionary Fauna ( Carlson, 2016 ; Harper et al, 2021 ; Harper et al, 2017 ; Sepkoski, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early Cambrian witnessed a great burst in diversity of animal body plans and biomineralized shell architectures around half a billion years ago (Briggs, 2015;Erwin, 2015Erwin, , 2020Budd and Jackson, 2016;Murdock, 2020;Yun et al, 2021;Zhang and Shu, 2021;Zhang et al, 2021c). The novel processes of biologically-controlled mineralization producing organic-inorganic composites (hard skeletons), in complex animals had played a vital role in the survival and fitness of early clades (Balthasar and Cusack, 2015;Cuif et al, 2010;Skovsted et al, 2008;Yun et al, 2022), and in turn built the fundamental blocks of complex marine ecosystems (Bicknell and Paterson, 2018;Buatois et al, 2020;Chen et al, 2022;Zhang et al, 2010Zhang et al, , 2020. Since the early Cambrian to the present day, this adaptive evolution has been demonstrated and continuously preserved in brachiopods, one of the key members of the Cambrian Evolutionary Fauna (Carlson, 2016;Harper et al, 2021Harper et al, , 2017Sepkoski, 1984).…”
Section: Introductionmentioning
confidence: 99%